2006
DOI: 10.1016/j.cub.2006.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Dmp53 Activates the Hippo Pathway to Promote Cell Death in Response to DNA Damage

Abstract: Developmental and environmental signals control a precise program of growth, proliferation, and cell death. This program ensures that animals reach, but do not exceed, their typical size . Understanding how cells sense the limits of tissue size and respond accordingly by exiting the cell cycle or undergoing apoptosis has important implications for both developmental and cancer biology. The Hippo (Hpo) pathway comprises the kinases Hpo and Warts/Lats (Wts), the adaptors Salvador (Sav) and Mob1 as a tumor suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 32 publications
2
53
0
1
Order By: Relevance
“…These findings corroborate the idea that the Hippo pathway plays an important role in mediating responses to xenobiotic stress. Activation of Hpo kinase occurs through phosphorylation of its kinase domain (on T195), 42 and consistent with this, we found increased levels of phosphorylated Hpo in flies fed with caffeine, suggesting that drug exposure promotes Hpo activation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings corroborate the idea that the Hippo pathway plays an important role in mediating responses to xenobiotic stress. Activation of Hpo kinase occurs through phosphorylation of its kinase domain (on T195), 42 and consistent with this, we found increased levels of phosphorylated Hpo in flies fed with caffeine, suggesting that drug exposure promotes Hpo activation.…”
Section: Discussionsupporting
confidence: 88%
“…41 Although the Hippo signaling pathway is best characterized for controlling tissue size, some work in Drosophila has linked the pathway to genotoxic stress 42 and alcohol-induced stress. 43 These studies, however, did not propose a molecular mechanism that could explain the role of Hippo as a modulator of stress response pathways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely accepted that p53 is a key determinant for cell death in response to anticancer drugs (Lowe et al, 1993(Lowe et al, , 1994. By using Drosophila genetics, Colombani et al (2006) discovered that Dmp53 (Drosophila melanogaster p53) activates Hippo, the Drosophila MST1 homolog, to induce cell death responses elicited by DNA-damaging ionizing radiation, suggesting a functional link between p53 and MST1. Moreover, it has been reported that p53-dependent apoptosis occurs through increasing oxidative stress (Johnson et al, 1996;Polyak et al, 1997;Li et al, 1999).…”
Section: Introductionmentioning
confidence: 99%